Phytochemical Profile And Antioxidant Activity Of Guazuma ulmifolia Leaves Extracts Using Different Solvent Extraction - Rafi, Mohamad; Meitary, Nadya; Anggraini Septaningsih, Dewi; Bintang, Maria (Indonesian Journal of Pharmacy, 2020)
Guazuma ulmifolia is one of the common tropical plants that has long been used as a traditional medicine to reduce body weight as slimming herbs and to lower the cholesterol in the body. The leaves of G. ulmifolia contain phenolics compound such as flavonoids and tannin that contributes to its biological activities. In this research, we determined the content of total phenolics, flavonoids, tannins, antioxidant activity, and FTIR spectrum profile from four extracts of G. ulmifolia leaves. The extraction method used in this study was stepwise maceration with different solvents n-hexane, ethyl acetate, ethanol, and water. The content of total phenolics and flavonoids were found high in ethanol extract of G. ulmifolia leaves with 35.42 and 44.85 mg QE/g dry powder, respectively. The highest content of total tannins was obtained in ethyl acetate extract of G. ulmifolia leaves as 0.55%. Antioxidant activity from four extracts of G. ulmifolia leaves was measured using DPPH, CUPRAC, and reducing power method. The highest antioxidant activity for DPPH and CUPRAC method was obtained in ethyl acetate extract with the antioxidant capacity as 55.47 and 98.17 µmol trolox/g dry powder, respectively. While using reducing power assay gives the capacity 176.75 µmol trolox/g dry powder in the water extract. The pattern of FTIR spectra from four extracts of G. ulmifolia leaves gives the distinct characteristics of each spectrum profile. Principal component analysis using FTIR spectrum shows good clustering for each extract with 94% data variability (PC1= 77% and PC2 = 17%). It can be concluded that each extract of G. ulmifolia leaves gives a distinct phytochemical profile (phenolics content, flavonoids, tannins, and FTIR spectrum) that contributes to the antioxidant activity. This antioxidant activity mainly influenced by the concentration of phenolic compounds, which is known to have antioxidant properties.